STUDENTS’ ENGAGEMENT IN NARROW LISTENING: A CASE OF AN EXTENSIVE LISTENING COURSE - Rozak, Refi Ranto; Matin, Moh. Fuadul (IKIP Siliwangi, 2024)
This article explores the implementation of Narrow Listening (NL) in an Extensive Listening (EL) course at a private English Education Department in Indonesia, addressing a gap in research regarding student engagement. Guided by Krashen's theory of input and repetitive listening practices, the study examines how NL can aid learners in achieving fluency and automaticity. Employing a case study approach, data were collected through observations of 42 multilingual students aged 18 to 19 during their first semester in the 2023/2024 academic year. Analysis revealed themes of both positive and negative behavioral, emotional, and cognitive engagement among students. While many demonstrated increased motivation and comprehension, some expressed anxiety and discomfort with certain learning tasks. The findings suggest that NL can significantly improve listening skills, boost student motivation, and facilitate a conducive learning environment, ultimately leading to better language acquisition outcomes. This study contributes valuable insights for educators aiming to enhance best practices in tertiary English education in Indonesia.